Using a Transdisciplinary Interpretive Lens to Broaden Reflections on Alleviating Poverty and Promoting Decent Work - Di Fabio, Annamaria; Maree, Jacobus G. (Frontiers in Psychology, 2016)
This article aims to broaden current reflections on definitions of decent work and poverty using a transdisciplinary interpretive lens comprising philosophical, juridical, economic, sociological, and psychological understandings. We (the authors) undertook an adapted systematic qualitative review to gather data on different perspectives on decent work and poverty. The article summarizes and compares reflections on the two constructs and proposes an enhancement of the current definition of decent work. The aim is to facilitate the identification and development of new research and intervention projects that can be implemented to promote fair and sustainable economic development, the provision of decent work, and the reduction of poverty globally. We believe that challenges should be dealt with pro-actively rather than reactively and that intervening at the level of primary prevention should lie at the heart of any strategy to promote decent work and alleviate poverty. Radical intervention is needed to ensure that future generations not only survive but develop, grow, and express themselves meaningfully through decent work